1997
DOI: 10.1161/01.cir.95.4.831
|View full text |Cite
|
Sign up to set email alerts
|

Human Connective Tissue Growth Factor Is Expressed in Advanced Atherosclerotic Lesions

Abstract: In the present study, we have shown for the first time that both hCTGF mRNA and protein are expressed in human arteries in vivo and that hCTGF may represent a novel factor expressed at high levels specifically in advanced lesions and may play a role in the development and progression of atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
213
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(223 citation statements)
references
References 24 publications
8
213
0
2
Order By: Relevance
“…In fact, previous in vivo studies have associated overexpression of CTGF with fibrotic disorders such as keloids, systemic sclerosis, and renal and lung fibrosis (19,25,32,40). CTGF is expressed at very high levels in atherosclerotic human vessels and localizes predominantly in areas with excessive deposition of extracellular matrix proteins (41). This likely reflects, as shown by others (42), the affinity of this growth factor to abundant matrix proteins such as collagens and fibronectin.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In fact, previous in vivo studies have associated overexpression of CTGF with fibrotic disorders such as keloids, systemic sclerosis, and renal and lung fibrosis (19,25,32,40). CTGF is expressed at very high levels in atherosclerotic human vessels and localizes predominantly in areas with excessive deposition of extracellular matrix proteins (41). This likely reflects, as shown by others (42), the affinity of this growth factor to abundant matrix proteins such as collagens and fibronectin.…”
Section: Discussionmentioning
confidence: 83%
“…Meanwhile, the local hemodynamic and metabolic changes that accompany the changes in mechanical stimulation induce, in turn, the expression and release of molecules involved in the regulation of muscle tone and contraction, i.e., angiotensin II, endothelin-1, and PTHrP (12,27,41,58). The rapid release of these factors is thought to be a general physiological response of tissues like the bladder wall that undergo continuous or periodic stretching and adjustment of muscle tonicity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CTGF expression is up-regulated in advanced atherosclerotic lesions, scleroderma, wound healing, renal and pulmonary fibrosis. 7,9,10,23,24 Since liver fibrosis is the hallmark of all chronic liver diseases, we were interested in investigating the role of CTGF in liver pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that TGF-b1 plays an essential role in the induction of fibrosis, 27 but other cytokines such as connective tissue growth factor (CTGF) act downstream of TGF-b1 to also facilitate progression of fibrosis. 28 It is therefore likely that expression level of TGF-b1 did not correlate with progression of pancreatic fibrosis. For the precise mechanisms of anti-inflammatory and anti-fibrogenic actions of pravastatin, we confirmed that pravastatin exerts antioxidative action in the pancreas, as previous studies have shown.…”
Section: Discussionmentioning
confidence: 99%